1999
DOI: 10.1046/j.1365-2249.1999.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine flow cytometry differentiates the clinical status of multiple sclerosis (MS) patients

Abstract: In this study we have examined intracellular cytokines in peripheral blood mononuclear cells (PBMC) of MS patients by flow cytometry (cytokine flow cytometry). MS progressive patients showed an increased number of cells producing interferon-gamma (IFN-gamma) after activation with phorbol 12-myristate 13-acetate and ionomycin, compared with patients with clinically inactive forms (P < 0001) and with healthy controls (P = 0001). These cells belonged to the CD4+ and CD8+ subsets in similar proportions. Clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…However, it was recently demonstrated that peripheral T cells from MS and healthy subjects significantly differ in surface phenotype or gene expression profiling (17,23,28). Using cDNA microarray, we have identified NR4A2 as a gene most significantly up-regulated in the peripheral T cells of MS (17).…”
Section: Discussionmentioning
confidence: 87%
“…However, it was recently demonstrated that peripheral T cells from MS and healthy subjects significantly differ in surface phenotype or gene expression profiling (17,23,28). Using cDNA microarray, we have identified NR4A2 as a gene most significantly up-regulated in the peripheral T cells of MS (17).…”
Section: Discussionmentioning
confidence: 87%
“…4,26 It is therefore suggested that Th cells from patients with VKH disease are apt to deviate toward the Th1 type, and activated Th cells in the inflammatory foci produce Th1 cytokines, thereby promoting inflammation. In addition, RA, 24,25 multiple sclerosis (MS) 27 and Behçet's disease 9 are also considered to be Th1-prone diseases. In contrast to these diseases, allergic diseases 28 and systemic lupus erythematosus (SLE) 29,30 are considered to be Th2-prone diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine treatments have been tried in some autoimmune diseases. 27,31 Inflammation of VKH disease may benefit from Th1 cytokine suppression or Th2 cytokine induction. However, artificial control of Th1/Th2 balance must be regulated cautiously, because reduction of excessive Th1 or Th2 cytokine production may precipitate the displacement of equilibrium toward another cytokine-prone condition.…”
Section: Discussionmentioning
confidence: 99%
“…All the test drugs were added at a concentration 10 g/ml and incubated for 4 h at 37C. After adding permeabilizing agent, phycoerythrin (PE)-labelled antimouse IL-2, IFN-gamma and IL-4 were added to the samples in separate falcon tubes and again incubated for 30 min, resuspended in PBS (pH 7.4) and acquired directly on the flow cytometer (BD LSR; Becton Dickinson) 21 .…”
Section: Screening Of Different Fractionations Of To-10mentioning
confidence: 99%
“…CA was added at concentrations of 0.25, 0.5, 1 and 2 g/ml and incubated for 4 h at 37C. PE-labelled antimouse IL-2, IFN-gamma and IL-4 were added to the samples, resuspended in PBS (pH 7.4) and acquired directly on the flow cytometer (BD LSR; Becton Dickinson) 21 .…”
Section: Effect Of Chicoric Acid On Th1/th2 Cytokines In Isolatedmentioning
confidence: 99%